Solar Panel Angle Orientation Influences Power Gain: A Case Study for KRG Location - Saeed, Ronak Ahmad; Sharif , Pshtiwan M.; Ali, Rezan Ahmed; Ahmed, Abubaker Aziz (Al-Nahrain Journal for Engineering Sciences, 2024)
Due to the Kurdistan regional government-KRG district mission potential towards huge solar energy power generation plant investments by global investors, a genuine study is required to explore the impact of PV-panels installation angles on power generation gain within all seasons duration as the KRG located in four season area which, affect the annual total power gain due to daylight duration effect in each season. The proposed study was conducted within a duration of “513” days utilizing three PV tilt installation angle tests of “ 30⁰, 35⁰, and 40⁰ ” with “ 545 watts single side PV plates” selecting the Erbil district area gaining a crucial role in maximizing energy output for comparison, Results presented a significant variation in power gain due to deviations in annual effective daylight duration effectively mostly a reduction in cold seasons within 25%-37.7% drops compared to the hot season, while the sunset and sunrise duration presented a significant influence of 5%-10% drops in power generated. The season change shows a significant influence of weather variation in each calendar on power gain annually. The installation orientation angle impact presented divergence in production within the cold season only. Process output can potentially unlock a novelty awareness of the investors toward innovative yield project optimization in the area as it will affect the annual power purchasing influence and production divergence with interest.